Metaphors in quechua riddles or watuchis: a study from cognitive semantics - Palomino, Niel (2023)
The purpose of the study is to identify, classify and expose the metaphors in Quechua riddles or watuchis, as well as the cognitive procedures for their creation. For this purpose, we will investigate the theory of metaphors proposed by Lakoff and Johnson (1980), in the book Metaphors We Live By. Methodologically, the corpus is composed of fifty riddles that were compiled and transcribed from the book Watuchikuna. This book was published in 1986 by the Centro Andino de Educación y Promoción (CADEP) "José María Arguedas" (Cusco-Peru). The results show that, in Quechua riddles, objects, fruits and animals are people; plants, animals; animals, objects; objects, living beings. Likewise, the body is a plant and the road is an object. The article concludes that most Quechua watuchis are ontological. Furthermore, in the perceptual, corporeal and cultural experience of the Quechua speaker the earth is a being that has life. Therefore, everything that exists in it has life or is personified to be expressed through the riddles.